Sterol composition of the Adriatic Sea algae Ulva lactuca, Codium dichotomum, Cystoseira adriatica and Fucus virsoides - RADOMIR KAPETANOVIC; DUSAN SLADIC; SIMEON POPO; MARIO ZLATOVIC; ZORAN KLJAJIC; MIROSLAV J. GASIC (Journal of the Serbian Chemical Society, 2005)
The sterol composition of two green algae and two brown algae from the South Adriatic was determined. In the green alga Ulva lactuca, the principal sterols were cholesterol and isofucosterol. In the brown alga Cystoseira adriatica, the main sterols were cholesterol and stigmast-5-en-3ß-ol, while the characteristic sterol of the brown algae, fucosterol, was found only in low concentration. The sterol fractions of the green alga Codium dichotomum and the brown alga Fucus virsoides contained practically only one sterol each, comprising more than 90 % of the total sterols (clerosterol in the former and fucosterol in the latter).